ETNOGRAFI KOMUNIKASI TRADISI HARI RAYA ENAM DI KELURAHAN PULAU KECAMATAN BANGKINANG - Awalia, Gusmiarti; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Tradition of Feast Day of Ramadhan Sixth tradition in Sub-District of Pulau is a tradition of the Bangkinang people who are passed down from generation to generation which is carried out on the 8th day of Shawwal every year in the form of a pilgrimage and eating bajambou. In this tradition there are a series of events of communication, social and cultural behavior in the Bangkinang speech community, especially to strengthen the inter-generational relationship. This study aims to find out the communicative situation, communicative events and communicative acts of the Feast Day of Ramadhan Sixth tradition in Sub-District of Pulau Bangkinang District.This study uses a qualitative method with an ethnographic approach. The research subjects consisted of 6 (six) speech people in Sub-District of Pulau Bangkinang District from traditional leaders and community leaders who knew, actively participated in and understood the traditional communication of the Feast Day of Ramadhan Sixth by using a purposive technique. Data collection is done through participant observation, in-depth interviews and documentation techniques. To perform data validity, the author uses techniques, perseverance of observation and adequacy of references.The results of the study concluded that the communicative situation in the tradition of Feast Day of Ramadhan Sixth tradition in Sub-District of Pulau Bangkinang District illustrates the situation that allows everyone to interact before and after the celebration of the Feast Day of Ramadhan Sixth tradition each year, including some preparations made. Communicative events include the entire set of components that build communication, namely genres or types of events, topics, objectives and functions, settings, participants, message forms, message content, sequence of actions, rules of interaction and norms of interpretation in the Feast Day of Ramadhan Sixth tradition. While communicative actions describe all ongoing communication activities that are unique or distinctive characteristics of the Feast Day of Ramadhan Sixth tradition, namely when the pilgrimage of the Bangkinang people from various social statuses, age groups and groups move together towards the cemetery in Sub-District of Pulau and surrounding areas to visit the grave and eat bajambou at a designated gathering place, such as inside and terrace of mosques or other places (Tuo's House).